Interactions, Complexity, Emergence: Toward an Image of God - Albright, Carol Rausch (Theology and science, 2021)
My thinking about religion and science and their relationship has developed through employment and related leadership in both areas of endeavor, along with research and writing. What do we make of the long history that preceded us: the great age of the universe and of our earth, the major extinctions of prior life? Why do human beings today have considerable freedom yet also experience suffering and evil? Current work in interaction and complexification, neuroscience and quantum physics, may provide clues to the modalities of a Creator. How may we begin to comprehend this? Poets and scientists provide hints.